Penggunaan Pendekatan Matematika Realistic Indonesia ( PMRI) Untuk Menigkatkan Hasil Belajar Siswa Kelas IV di Sekolah Dasar - Asri Putri Anugraini; Dwi Purnomo (Peneliti.net, 2022)
Mathematics is a lesson that forms thinking patterns, organizing patterns, logical proofs. Elementary school students will be able to understand mathematics with concrete operations, therefore learning in elementary school must begin by presenting concrete or realistic problems so that students can carry out the learning process directly and real. The results of observations and observations as well as interviews conducted by researchers to classroom teachers in grade IV, the most prominent problem is the low value of student learning outcomes in several subjects, especially mathematics. Students look busy themselves, not immediately working on questions but playing, arranging writing tools, doing things that should not be done during the learning process, for example cutting paper, drawing cartoons. Realistic Mathematics Education Approach (PMRI) is a learning theory in mathematics that provides human activities to be learned by working on mathematical problems. The application of the PMRI approach can improve students' mathematics learning outcomes. This can be seen from the increase in the average value of student learning outcomes which previously averaged 60.2% of students' mathematics learning outcomes in the first cycle to 84.35% in the second cycle. Student responses to the implementation of the PMRI approach were very positive. This is indicated by an increase in the average positive response of students from 69% in the first cycle to 80.7 in the second cycle